2018
DOI: 10.3390/s18082504
|View full text |Cite
|
Sign up to set email alerts
|

Portable System for Real-Time Detection of Stress Level

Abstract: Currently, mental stress is a major problem in our society. It is related to a wide variety of diseases and is mainly caused by daily-life factors. The use of mobile technology for healthcare purposes has dramatically increased during the last few years. In particular, for out-of-lab stress detection, a considerable number of biosignal-based methods and systems have been proposed. However, these approaches have not matured yet into applications that are reliable and useful enough to significantly improve peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 53 publications
1
31
0
2
Order By: Relevance
“…Although Fp1 is known as a suboptimal location for detecting human drowsiness, EEG measurements taken at Fp1 have been demonstrated to be correlated with drowsiness [40]. Furthermore, it is well-established that frontal area activity correlates with human emotion and stress [41,42]. When drowsiness can be estimated using the measurements from Fp1, the EEG can be used to infer other mental states of the user.…”
Section: Model Developmentmentioning
confidence: 99%
“…Although Fp1 is known as a suboptimal location for detecting human drowsiness, EEG measurements taken at Fp1 have been demonstrated to be correlated with drowsiness [40]. Furthermore, it is well-established that frontal area activity correlates with human emotion and stress [41,42]. When drowsiness can be estimated using the measurements from Fp1, the EEG can be used to infer other mental states of the user.…”
Section: Model Developmentmentioning
confidence: 99%
“…After a stress inducing experiment, they concluded that the selected biosignals, their processing methods and the machine learning algorithm gave optimistic results about the precise detection and classification of stress levels. Minguillon et al (2018) [75] proposed the collection and statistical analysis of a multitude of signals for stress level characterization (EEG, ECG, EMG, GSR) summarizing the existing literature.…”
Section: -Implementations Of the Analysis Methodsmentioning
confidence: 99%
“…Secara umum, kami menganggap bahwa, kenaikan nilai relative power beta menunjukkan keadaan tubuh subjek yang terkesan gelisah dan menimbulkan peningkatan gelombang otak sehingga manifestasi dari stres seperti gelisah, frustasi, ataupun marah yang muncul saat distimulasi oleh permainan ini. Hal ini juga ditunjukkan dari studi terdahulu yang menggunakan gelombang beta sebagai salah satu fitur parameter EEG dalam mendeteksi stres [15].…”
Section: Hasil Dan Analisa Pembahasanunclassified